Methylome and transcriptome profiles in three yak tissues revealed that DNA methylation and the transcription factor ZGPAT co-regulate milk production - Jinwei Xin; Zhixin Chai; Chengfu Zhang; Qiang Zhang; Yong Zhu; Hanwen Cao; Cidan Yangji; Xiaoying Chen; Hui Jiang; Jincheng Zhong; Qiumei Ji (BMC Genomics, 2020)
Abstract Background Domestic yaks play an indispensable role in sustaining the livelihood of Tibetans and other ethnic groups on the Qinghai-Tibetan Plateau (QTP), by providing milk and meat. They have evolved numerous physiological adaptations to high-altitude environment, including strong blood oxygen transportation capabilities and high metabolism. The roles of DNA methylation and gene expression in milk production and high-altitudes adaptation need further exploration. Results We performed genome-wide DNA methylome and transcriptome analyses of breast, lung, and biceps brachii muscle tissues from yaks of different ages. We identified 432,350 differentially methylated regions (DMRs) across the age groups within each tissue. The post-mature breast tissue had considerably more differentially methylated regions (155,957) than that from the three younger age groups. Hypomethylated genes with high expression levels might regulate milk production by influencing protein processing in the endoplasmic reticulum. According to weighted gene correlation network analysis, the “hub” gene ZGPAT was highly expressed in the post-mature breast tissue, indicating that it potentially regulates the transcription of 280 genes that influence protein synthesis, processing, and secretion. The tissue network analysis indicated that high expression of HIF1A regulates energy metabolism in the lung. Conclusions This study provides a basis for understanding the epigenetic mechanisms underlying milk production in yaks, and the results offer insight to breeding programs aimed at improving milk production.